2015
DOI: 10.1295/koron.2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Network Structure and the Drug Release Characteristics of Agar Gel and Xanthan Gum-Locust Bean Gum Complex Gel

Abstract: 1 大蔵製薬 (株) 研究開発第一部 (〠 611-0041 宇治市槙島町 十一 65-1) * 2 山形大学大学院理工学研究科機械システム工学専攻ソフ ト & ウェットマター工学研究室 (〠 992-8510 米沢市城南 4-3-16) * 3 岐阜薬科大学大学院薬学研究科薬科学専攻薬物送達学大 講座製剤学研究室 (〠 501-1196 岐阜市大学西 1-25-4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is known that pectin gelation is affected by a variety of ions. 20,21) For example, in this study, gelation occurred in the formulation in which GDL was eliminated from the basic formulation shown in Table 1 after addition of citric acid solution at pH >3; however, in cases in which citric acid solution with pH of 2.9 and buffer solution with pH of >3 were added or in which sodium chloride was added, no gelation occurred. The causes may be that pectin does not dissolve to give a solution with low pH, and the gelation ability of pectin was weakened by the presence of sodium.…”
Section: Effect Of Metal Ions In Water Added To the Dry Jelly On Gelation Propertiesmentioning
confidence: 62%
“…It is known that pectin gelation is affected by a variety of ions. 20,21) For example, in this study, gelation occurred in the formulation in which GDL was eliminated from the basic formulation shown in Table 1 after addition of citric acid solution at pH >3; however, in cases in which citric acid solution with pH of 2.9 and buffer solution with pH of >3 were added or in which sodium chloride was added, no gelation occurred. The causes may be that pectin does not dissolve to give a solution with low pH, and the gelation ability of pectin was weakened by the presence of sodium.…”
Section: Effect Of Metal Ions In Water Added To the Dry Jelly On Gelation Propertiesmentioning
confidence: 62%
“…32,33) We previously reported that the Ag gel and Xa-Lo combination gel have networks that provide different levels of dense structures, which may determine the release properties of incorporated pharmaceutical agents. 28) For this test, the gels were prepared by combining Ag and Xa-Lo at various ratios according to the combinations specified in Table 1. Then, we examined the effects of the different combinations on the diffusion rate of the pharmaceutical agents and changes in their release properties from the gels.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that higher Ag concentrations were associated with higher breaking stress values, and closer distance between the points of the crosslinked structure of the gel network produced denser networks. 28) In addition, the release properties of the AAP embedded in the gel remained the same regardless of Ag concentrations. 28) The results of the F-Na diffusion coefficient test are consistent with the findings of our previous study where higher Ag gel concentrations generated denser networks.…”
Section: Effect Of Model Substance Concentrations On Diffusion Coeffimentioning
confidence: 91%
See 1 more Smart Citation